Peptide stapling by late-stage Suzuki–Miyaura cross-coupling - Gruß, Hendrik; Feiner, Rebecca C.; Mseya, Ridhiwan; Schröder, David C.; Jewgiński, Michał; Müller, Kristian M.; Latajka, Rafał; Marion, Antoine; Sewald, Norbert (Beilstein Journal of Organic Chemistry, 2022)
The development of peptide stapling techniques to stabilise α-helical secondary structure motifs of peptides led to the design of modulators of protein–protein interactions, which had been considered undruggable for a long time. We disclose a novel approach towards peptide stapling utilising macrocyclisation by late-stage Suzuki–Miyaura cross-coupling of bromotryptophan-containing peptides of the catenin-binding domain of axin. Optimisation of the linker length in order to find a compromise between both sufficient linker rigidity and flexibility resulted in a peptide with an increased α-helicity and enhanced binding affinity to its native binding partner β-catenin. An increased proteolytic stability against proteinase K has been demonstrated.
Keywords: accelerated molecular dynamics; halotryptophan; intrinsically disordered peptides; late-stage diversification; macrocyclisation; molecular dynamics; stapled peptides; Suzuki–Miyaura cross-coupling

(untitled) - Valeur, E.; Guéret, S. M.; Adihou, H.; Gopalakrishnan, R.; Lemurell, M.; Waldmann, H.; Grossmann, T. N.; Plowright, A. T. (Angew. Chem., Int. Ed., 2017)

(untitled) - Valeur, E.; Guéret, S. M.; Adihou, H.; Gopalakrishnan, R.; Lemurell, M.; Waldmann, H.; Grossmann, T. N.; Plowright, A. T. (Angew. Chem., 2017)

(untitled) - Verdine, G. L.; Hilinski, G. J. (Drug Discovery Today: Technol., 2012)

(untitled) - Blackwell, H. E.; Grubbs, R. H. (Angew. Chem., Int. Ed., 1998)

(untitled) - Blackwell, H. E.; Grubbs, R. H. (Angew. Chem., 1998)

(untitled) - Schafmeister, C. E.; Po, J.; Verdine, G. L. (J. Am. Chem. Soc., 2000)

(untitled) - Kim, Y.-W.; Grossmann, T. N.; Verdine, G. L. (Nat. Protoc., 2011)

(untitled) - Walensky, L. D.; Bird, G. H. (J. Med. Chem., 2014)

Protein-protein interactions in drug discovery - Dömling, A. (Wiley-VCH, 2013)

(untitled) - Lau, Y. H.; de Andrade, P.; Wu, Y.; Spring, D. R. (Chem. Soc. Rev., 2015)

(untitled) - Felix, A. M.; Heimer, E. P.; Wang, C. T.; Lambros, T. J.; Fournier, A.; Mowles, T. F.; Maines, S.; Campbell, R. M.; Wegrzynski, B. B.; Toome, V.; Fry, D.; Madison, V. S. (Int. J. Pept. Protein Res., 1988)

(untitled) - Shepherd, N. E.; Hoang, H. N.; Abbenante, G.; Fairlie, D. P. (J. Am. Chem. Soc., 2005)

(untitled) - Jackson, D. Y.; King, D. S.; Chmielewski, J.; Singh, S.; Schultz, P. G. (J. Am. Chem. Soc., 1991)

(untitled) - Brunel, F. M.; Dawson, P. E. (Chem. Commun., 2005)

(untitled) - Brunel, F. M.; Zwick, M. B.; Cardoso, R. M. F.; Nelson, J. D.; Wilson, I. A.; Burton, D. R.; Dawson, P. E. (J. Virol., 2006)

(untitled) - Wang, Y.; Chou, D. H.-C. (Angew. Chem., Int. Ed., 2015)

(untitled) - Wang, Y.; Chou, D. H.-C. (Angew. Chem., 2015)

(untitled) - Zhang, G.; Barragan, F.; Wilson, K.; Levy, N.; Herskovits, A.; Sapozhnikov, M.; Rodríguez, Y.; Kelmendi, L.; Alkasimi, H.; Korsmo, H.; Chowdhury, M.; Gerona‐Navarro, G. (Angew. Chem., Int. Ed., 2018)

(untitled) - Zhang, G.; Barragan, F.; Wilson, K.; Levy, N.; Herskovits, A.; Sapozhnikov, M.; Rodríguez, Y.; Kelmendi, L.; Alkasimi, H.; Korsmo, H.; Chowdhury, M.; Gerona‐Navarro, G. (Angew. Chem., 2018)

(untitled) - Jo, H.; Meinhardt, N.; Wu, Y.; Kulkarni, S.; Hu, X.; Low, K. E.; Davies, P. L.; DeGrado, W. F.; Greenbaum, D. C. (J. Am. Chem. Soc., 2012)

(untitled) - Scrima, M.; Le Chevalier-Isaad, A.; Rovero, P.; Papini, A. M.; Chorev, M.; D'Ursi, A. M. (Eur. J. Org. Chem., 2010)

(untitled) - Kawamoto, S. A.; Coleska, A.; Ran, X.; Yi, H.; Yang, C.-Y.; Wang, S. (J. Med. Chem., 2012)

(untitled) - Haney, C. M.; Loch, M. T.; Horne, W. S. (Chem. Commun., 2011)

(untitled) - Madden, M. M.; Muppidi, A.; Li, Z.; Li, X.; Chen, J.; Lin, Q. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Vasco, A. V.; Méndez, Y.; Porzel, A.; Balbach, J.; Wessjohann, L. A.; Rivera, D. G. (Bioconjugate Chem., 2019)

(untitled) - Ricardo, M. G.; Llanes, D.; Wessjohann, L. A.; Rivera, D. G. (Angew. Chem., Int. Ed., 2019)

(untitled) - Ricardo, M. G.; Llanes, D.; Wessjohann, L. A.; Rivera, D. G. (Angew. Chem., 2019)

(untitled) - Ricardo, M. G.; Ali, A. M.; Plewka, J.; Surmiak, E.; Labuzek, B.; Neochoritis, C. G.; Atmaj, J.; Skalniak, L.; Zhang, R.; Holak, T. A.; Groves, M.; Rivera, D. G.; et al. (Angew. Chem., Int. Ed., 2020)

(untitled) - Ricardo, M. G.; Ali, A. M.; Plewka, J.; Surmiak, E.; Labuzek, B.; Neochoritis, C. G.; Atmaj, J.; Skalniak, L.; Zhang, R.; Holak, T. A.; Groves, M.; Rivera, D. G.; et al. (Angew. Chem., 2020)

(untitled) - Reguera, L.; Rivera, D. G. (Chem. Rev., 2019)

(untitled) - Ceballos, J.; Grinhagena, E.; Sangouard, G.; Heinis, C.; Waser, J. (Angew. Chem., Int. Ed., 2021)

(untitled) - Ceballos, J.; Grinhagena, E.; Sangouard, G.; Heinis, C.; Waser, J. (Angew. Chem., 2021)

(untitled) - Kumita, J. R.; Smart, O. S.; Woolley, G. A. (Proc. Natl. Acad. Sci. U. S. A., 2000)

(untitled) - Flint, D. G.; Kumita, J. R.; Smart, O. S.; Woolley, G. A. (Chem. Biol., 2002)

(untitled) - Zhang, C.; Vinogradova, E. V.; Spokoyny, A. M.; Buchwald, S. L.; Pentelute, B. L. (Angew. Chem., Int. Ed., 2019)

(untitled) - Zhang, C.; Vinogradova, E. V.; Spokoyny, A. M.; Buchwald, S. L.; Pentelute, B. L. (Angew. Chem., 2019)

(untitled) - Wang, W.; Lorion, M. M.; Shah, J.; Kapdi, A. R.; Ackermann, L. (Angew. Chem., Int. Ed., 2018)

(untitled) - Vinogradova, E. V.; Zhang, C.; Spokoyny, A. M.; Pentelute, B. L.; Buchwald, S. L. (Nature, 2015)

(untitled) - Rojas, A. J.; Pentelute, B. L.; Buchwald, S. L. (Org. Lett., 2017)

(untitled) - Rojas, A. J.; Zhang, C.; Vinogradova, E. V.; Buchwald, N. H.; Reilly, J.; Pentelute, B. L.; Buchwald, S. L. (Chem. Sci., 2017)

(untitled) - Lee, H. G.; Lautrette, G.; Pentelute, B. L.; Buchwald, S. L. (Angew. Chem., Int. Ed., 2017)

(untitled) - Lee, H. G.; Lautrette, G.; Pentelute, B. L.; Buchwald, S. L. (Angew. Chem., 2017)

(untitled) - Ma, B.; Elkayam, T.; Wolfson, H.; Nussinov, R. (Proc. Natl. Acad. Sci. U. S. A., 2003)

(untitled) - Ruiz-Rodríguez, J.; Albericio, F.; Lavilla, R. (Chem. – Eur. J., 2010)

(untitled) - Williams, T. J.; Reay, A. J.; Whitwood, A. C.; Fairlamb, I. J. S. (Chem. Commun., 2014)

(untitled) - Zhu, Y.; Bauer, M.; Ackermann, L. (Chem. – Eur. J., 2015)

(untitled) - Reay, A. J.; Williams, T. J.; Fairlamb, I. J. S. (Org. Biomol. Chem., 2015)

(untitled) - Reay, A. J.; Hammarback, L. A.; Bray, J. T. W.; Sheridan, T.; Turnbull, D.; Whitwood, A. C.; Fairlamb, I. J. S. (ACS Catal., 2017)

(untitled) - Dong, H.; Limberakis, C.; Liras, S.; Price, D.; James, K. (Chem. Commun., 2012)

(untitled) - Mendive-Tapia, L.; Preciado, S.; García, J.; Ramón, R.; Kielland, N.; Albericio, F.; Lavilla, R. (Nat. Commun., 2015)

(untitled) - Noisier, A. F. M.; García, J.; Ionuţ, I. A.; Albericio, F. (Angew. Chem., Int. Ed., 2017)

(untitled) - Noisier, A. F. M.; García, J.; Ionuţ, I. A.; Albericio, F. (Angew. Chem., 2017)

(untitled) - Schnepel, C.; Sewald, N. (Chem. – Eur. J., 2017)

(untitled) - Minges, H.; Sewald, N. (ChemCatChem, 2020)

Amino Acids, Peptides and Proteins - Dachwitz, S.; Widmann, C.; Frese, M.; Niemann, H. H.; Sewald, N. (Enzymatic halogenation: enzyme mining, mechanisms, and implementation in reaction cascades, 2019)

(untitled) - Schnepel, C.; Minges, H.; Frese, M.; Sewald, N. (Angew. Chem., Int. Ed., 2016)

(untitled) - Schnepel, C.; Minges, H.; Frese, M.; Sewald, N. (Angew. Chem., 2016)

(untitled) - Frese, M.; Schnepel, C.; Minges, H.; Voß, H.; Feiner, R.; Sewald, N. (ChemCatChem, 2016)

(untitled) - Gruß, H.; Belu, C.; Bernhard, L. M.; Merschel, A.; Sewald, N. (Chem. – Eur. J., 2019)

(untitled) - Pubill‐Ulldemolins, C.; Sharma, S. V.; Cartmell, C.; Zhao, J.; Cárdenas, P.; Goss, R. J. M. (Chem. – Eur. J., 2019)

(untitled) - Sharma, S. V.; Tong, X.; Pubill-Ulldemolins, C.; Cartmell, C.; Bogosyan, E. J. A.; Rackham, E. J.; Marelli, E.; Hamed, R. B.; Goss, R. J. M. (Nat. Commun., 2017)

(untitled) - Willemse, T.; Van Imp, K.; Goss, R. J. M.; Van Vlijmen, H. W. T.; Schepens, W.; Maes, B. U. W.; Ballet, S. (ChemCatChem, 2015)

(untitled) - Corr, M. J.; Sharma, S. V.; Pubill-Ulldemolins, C.; Bown, R. T.; Poirot, P.; Smith, D. R. M.; Cartmell, C.; Abou Fayad, A.; Goss, R. J. M. (Chem. Sci., 2017)

(untitled) - Roy, A. D.; Grüschow, S.; Cairns, N.; Goss, R. J. M. (J. Am. Chem. Soc., 2010)

(untitled) - Dachwitz, S.; Duwe, D. H.; Wang, Y. H.; Gruß, H.; Hannappel, Y.; Hellweg, T.; Sewald, N. (Chem. – Eur. J., 2020)

(untitled) - Gruß, H.; Sewald, N. (Chem. – Eur. J., 2020)

(untitled) - Kemker, I.; Schröder, D. C.; Feiner, R. C.; Müller, K. M.; Marion, A.; Sewald, N. (J. Med. Chem., 2021)

(untitled) - Kemker, I.; Feiner, R. C.; Müller, K. M.; Sewald, N. (ChemBioChem, 2020)

(untitled) - Ghabraie, E.; Kemker, I.; Tonali, N.; Ismail, M.; Dodero, V. I.; Sewald, N. (Chem. – Eur. J., 2020)

(untitled) - Schnepel, C.; Dodero, V. I.; Sewald, N. (Chem. – Eur. J., 2021)

(untitled) - García-Pindado, J.; Willemse, T.; Goss, R.; Maes, B. U. W.; Giralt, E.; Ballet, S.; Teixidó, M. (Biopolymers, 2018)

(untitled) - Kemker, I.; Schnepel, C.; Schröder, D. C.; Marion, A.; Sewald, N. (J. Med. Chem., 2019)

(untitled) - Frese, M.; Sewald, N. (Angew. Chem., Int. Ed., 2015)

(untitled) - Frese, M.; Sewald, N. (Angew. Chem., 2015)

(untitled) - Xing, Y.; Clements, W. K.; Kimelman, D.; Xu, W. (Genes Dev., 2003)

(untitled) - Clevers, H.; Nusse, R. (Cell, 2012)

(untitled) - Grossmann, T. N.; Yeh, J. T.-H.; Bowman, B. R.; Chu, Q.; Moellering, R. E.; Verdine, G. L. (Proc. Natl. Acad. Sci. U. S. A., 2012)

(untitled) - Afonso, A.; Cussó, O.; Feliu, L.; Planas, M. (Eur. J. Org. Chem., 2012)

(untitled) - Guan, Z.; Yates, N. A.; Bakhtiar, R. (J. Am. Soc. Mass Spectrom., 2003)

(untitled) - Afonso, A.; Feliu, L.; Planas, M. (Tetrahedron, 2011)

(untitled) - Sönnichsen, F. D.; Van Eyk, J. E.; Hodges, R. S.; Sykes, B. D. (Biochemistry, 1992)

(untitled) - Shinohara, T.; Deng, H.; Snapper, M. L.; Hoveyda, A. H. (J. Am. Chem. Soc., 2005)

(untitled) - Thakkar, B. S.; Svendsen, J.-S. M.; Engh, R. A. (J. Phys. Chem. A, 2017)

(untitled) - Nguyen, K.; Iskandar, M.; Rabenstein, D. L. (J. Phys. Chem. B, 2010)

AMBER18 (University of California, 2018)

(untitled) - Hamelberg, D.; Mongan, J.; McCammon, J. A. (J. Chem. Phys., 2004)

(untitled) - Miao, Y.; Feixas, F.; Eun, C.; McCammon, J. A. (J. Comput. Chem., 2015)

(untitled) - Duan, L.; Guo, X.; Cong, Y.; Feng, G.; Li, Y.; Zhang, J. Z. H. (Front. Chem. (Lausanne, Switz.), 2019)

(untitled) - Kamenik, A. S.; Lessel, U.; Fuchs, J. E.; Fox, T.; Liedl, K. R. (J. Chem. Inf. Model., 2018)

(untitled) - Maier, J. A.; Martinez, C.; Kasavajhala, K.; Wickstrom, L.; Hauser, K. E.; Simmerling, C. (J. Chem. Theory Comput., 2015)

(untitled) - Wang, J.; Wolf, R. M.; Caldwell, J. W.; Kollman, P. A.; Case, D. A. (J. Comput. Chem., 2004)

(untitled) - Sinko, W.; Miao, Y.; de Oliveira, C. A. F.; McCammon, J. A. (J. Phys. Chem. B, 2013)

(untitled) - Miao, Y.; Sinko, W.; Pierce, L.; Bucher, D.; Walker, R. C.; McCammon, J. A. (J. Chem. Theory Comput., 2014)

(untitled) - Noé, F.; Rosta, E. (J. Chem. Phys., 2019)

(untitled) - Toenjes, S. T.; Gustafson, J. L. (Future Med. Chem., 2018)